THE IMPACT OF PRENUPTIAL AGREEMENTS ON THE RIGHTS AND OBLIGATIONS OF HUSBAND AND WIFE - Imran, Fauziah Tri Septiana; Elimartati, Elimartati; Fitri, Hidayati (Institut Agama Islam Negeri Batusangkar, 2024)
This study analyzes the content and practice of premarital agreements, as well as the impact of making a marriage agreement on the rights and obligations of husband and wife in Talawi Hilir Village, Talawi District. This research is a field research using a qualitative approach. In its implementation, it has a positive and negative impact on two married couples, making a prenuptial agreement has a positive impact, namely the rights and obligations of husband and wife have been regulated in a prenuptial agreement so that it makes it easier to carry out their role as husband and wife in fulfilling their rights and obligations.